2014
DOI: 10.1007/s12250-014-3452-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan on tobacco mosaic virus (TMV) accumulation, hydrolase activity, and morphological abnormalities of the viral particles in leaves of N. tabacum L. cv. Samsun

Abstract: The effect of chitosan on the development of infection caused by Tobacco mosaic virus (TMV) in leaves of Nicotiana tabacum L. cv. Samsun has been studied. It was shown that the infectivity and viral coat protein content in leaves inoculated with a mixture of TMV (2 μg/mL) and chitosan (1 mg/mL) were lower in the early period of infection (3 days after inoculation), by 63% and 66% respectively, than in leaves inoculated with TMV only. Treatment of leaves with chitosan 24 h before inoculation with TMV also cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…Electron microscope examination revealed that the TMV particles were directly affected by nanoparticles, resulting in decreased viral particles, and the majority of them twisted together and tied into a bundle, leading to virus structure rupture [55,59]. In agreement with our results, the DAS-ELISA showed the efficacy of chitosan to control CMV, PVX, and TMV infections [51,58,60]. The authors suggested that chitosan increased plant resistance through enhancing ribonuclease activity and callose deposition as well as increasing the activity of hydrolases (proteases and RNases).…”
Section: Antiviral Activity Of Chitosan/dextran Nanoparticles (Cdnps)...supporting
confidence: 89%
See 2 more Smart Citations
“…Electron microscope examination revealed that the TMV particles were directly affected by nanoparticles, resulting in decreased viral particles, and the majority of them twisted together and tied into a bundle, leading to virus structure rupture [55,59]. In agreement with our results, the DAS-ELISA showed the efficacy of chitosan to control CMV, PVX, and TMV infections [51,58,60]. The authors suggested that chitosan increased plant resistance through enhancing ribonuclease activity and callose deposition as well as increasing the activity of hydrolases (proteases and RNases).…”
Section: Antiviral Activity Of Chitosan/dextran Nanoparticles (Cdnps)...supporting
confidence: 89%
“…In this context, foliar application and treatment of tomato plants with ZnO NPs and Ag NPs reduced viral accumulation levels inside plant tissues and decreased disease severity [26,57]. In agreement with our results, chitosan nanoparticles might attach to virus particles, inhibit nucleic acid replication inside infected cells, as well as boost plant immunity and antioxidant defense systems [51,58]. Electron microscope examination revealed that the TMV particles were directly affected by nanoparticles, resulting in decreased viral particles, and the majority of them twisted together and tied into a bundle, leading to virus structure rupture [55,59].…”
Section: Antiviral Activity Of Chitosan/dextran Nanoparticles (Cdnps)...supporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, chitosan in formulation with plant growth promoting rhizobacteria (PGRP) conferred resistance to leaf curl virus in tomato plant [ 79 ]. Also, chitosan was found effective against squash mosaic virus (SMV) [ 80 , 81 ]. Furthermore, Chirkov et al [ 18 ] hypothesized that there might be some peculiar properties of the host plant which initiate the antiviral reaction(s) after chitosan treatment.…”
Section: Antimicrobial Activity Of Chitosanmentioning
confidence: 99%
“…CS is also used as a conventional fungicide in both preharvest (Feliziani et al, 2015) and post-harvest applications (Sivakumar et al, 2016;Zhang et al, 2015). CS applicationinduced response against potato virus X and tomato mosaic virus was reported by (Chirkov et al, 2001;Jia et al, 2016;Nagorskaya et al, 2014). CS perception in the plant's variation in the ion fluxes and membrane depolarization (Iriti and Varoni, 2015) and also recognized by the plant as a pathogen-mimicking stimulus, but the identification of a CS receptor is still mysterious (Malerba and Cerana, 2016;Povero et al, 2011).…”
mentioning
confidence: 99%